Analysis of the impact of man-made harmful waste on the soil by X-ray fluorescence method - Myrzabaev, A.B.; Golovanov, D.L.; Urbaniak, Ya.; Kusherbaev, S.A.; Bodeev М.Т. (Fundamental and Experimental Biology, 2022)
As the technogenic load increases from year to year, the soil loses its ability to provide plants with various nutrients, air, water, heat, biological and physico-chemical environment. The reason is an increase in heavy metal compounds in the soil, which leads to its degradation. The presence of heavy metals in the ecosystem, such as Pb, Cr, As, is toxic to humans and biosystems even at low concentrations. Anthropogenic pollution of the environment by heavy metals (industry, mining and smelting of ores, transport, agriculture) increases over time. Currently, soil contamination with heavy metals and its impact on the biosphere are increasingly being studied. This is especially observed in large industrially urbanized regions, where there is a large accumulation of hazardous waste that does not decompose in nature and is stored for a long time. To identify anthropogenic pollution of the environment with heavy metals, samples were taken from various soil horizons of the city of Zhezkazgan and adjacent regions. The chemical compositions of the taken samples were determined by X-ray fluorescence. Analytical work was carried out in the laboratory of the Department ofLandscape Geochemistry and Soil Geography of Lomonosov Moscow State University. We analyzed the quantitative content of chemical elements in the soils of Zhezkazgan and adjacent zones I (As, Zn, Cd, Pb, Hg, Se), II (Co, Ni, Mo, Cu, Cr), III (Ba, V, W, Mn, Sr) hazard levels.